Effects of pressure on thermal contact resistance for rough mating surfaces - M. Z. Abdullah,; Y. C. Yau,; Z. A. Zainal Alauddin, and; K. N. Seetharamu (ASEAN Journal on Science and Technology for Development, 2001)
Thermal contact resistance has been studied experimentally to  investigate the effect of pressure between two aluminium or two brass rough surfaces at three different heat flux levels. Three different rough surfaces are considered in the range of 2.63 to 40.69?m. It is demonstrated that the thermal contact resistance reduces significantly with pressure for both materials, the harder material gives higher thermal contact resistance as expected